The Obesity Epidemic - Taylor, Monica M. author. aut Link
XI, 86 p.
Keywords: This book addresses the obesity epidemic from a political, economic and social perspective. Examining the populations that suffer the greatest from political and economic decision-making associated with obesity prevalence, this book utilizes a contemporary framework to discuss obesity. While it does examine the behavioral risks associated with rising obesity rates, it also explores the political level, by evaluating theories in social justice and the political economy that foster or restrict at-risk behaviors. It considers the economic context through rising income inequality levels in the US. It also critiques the actions of higher institutions, including transnational corporations, as social contributors to this epidemic. Finally, it compares global and national challenges of the epidemic.